‘I am absolutely shattered’: The impact of chronic low back pain on Australian Aboriginal people - Lin, Ivan; O'Sullivan, P; Coffin, Ja; Mak, Donna; Toussaint, S; Straker, Leon (John Wiley & Sons Ltd., 2012)
Background: Aboriginal people in Australia have been uniquely identified as less susceptible to chronic low back pain (CLBP) disability when compared to non-Aboriginal populations, reportedly due to cultural beliefs about pain. A qualitative, culturally secure research approach was used to explore this assumption. Methods: In-depth interviews were undertaken with 32 Aboriginal men and women with CLBP in regional and remote areas of Western Australia. Interviews were conducted collaboratively with male and female Aboriginal co-investigators, and with the support of local Aboriginal community organizations. A primary focus was to investigate the impact of CLBP from the perspective of Aboriginal people living with the condition. Results: The experience of CLBP was found to be multidimensional, impacting on activities of daily life, employment, sport and family participation, emotional and cultural well-being. Conclusions: Contrary to previous assumptions, CLBP is profoundly disabling for some Aboriginal people and a priority health concern. Issues of gender, cultural obligations and the emotional consequences of CLBP are important consideration for health care. These findings, and the contextual approach used to gain an in-depth understanding of CLBP, may be relevant to populations elsewhere.